VALPROATE INDUCED HYPERAMMONEMIAWITH DERANGED LIVER FUNCTION - Tripathy, Ratikanta; Majhi, Jatin Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Valproate is one of the most prescribed anti-epileptic drugs. It could cause a rise in serum ammonia level in patients, especially children and young adults. This presents with altered orientation, lethargy, focal neurological deficit, etc. If this condition is not treated, then it can be fatal. There is a good correlation between fall of ammonia level and clinical improvement. We, here, present a case of valproate induced hyperammonemia and deranged liver function in a child of 1-year age admitted to a tertiary care hospital. Keywords: Hyperammonemia, Hyperammonemic encephalopathy, Valproate.